QUALITY OF LIFE IN PATIENTS WITH CHRONIC HEART FAILURE OF ISCHEMIC ETIOLOGY: ROLE OF ANXIETY AND DEPRESSIVE DISORDERS - Vatutin, N. T.; Khrystychenko, М. А.; Keting, E. V. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2015)
OBJECTIVE: To evaluate the quality of life (QоL) in patients with anxiety and depressive disorders (ADD) and chronic heart failure (CHF) of ischemic origin.METHODS: The study involved 142 patients (85 men and 57 women, mean age 66,4 ± 10,5 years) with CHF NYHA II-IV functional class. To identify anxiety and depression were used Hospital Anxiety and Depression Scale (HADS), the scales of the Spielberger-Hanin and Beck’s, QоL – Minnesota QоL Questionnaire “Living with Heart Failure» (MLHFQ) and the SF-36 questionnaire.RESULTS: ADD prevalence in patients with CHF of ischemic etiology was 78.1 %, with the largest share in the combination of anxiety and depressive disorders. The deterioration of QoL was observed in all patients with CHF, but the most pronounced decrease in its registered patients with a combination of anxiety and depression. The obtained data was processed using the statistical suite Statistica 6.0 for Windows and presented as M ± σ (mean ± standard deviation).CONCLUSIONS: The presence of ADD leads to a significant decrease in QoL of patients with CHF, the most significant of its deterioration observed in the combination of anxiety and depression.The article presents the results of investigation of gastric mucosal microcirculation with the help of laser-Doppler flowmetry in acute phase of duodenal ulcer during 7 and 14-day eradication therapy. The study enabled to obtain some data on effectiveness of the two therapeutic eradication regimens as well as their im-pact on gastric mucosal microcirculation in the process of ulcer defects healing.